Carbon nanotube sheet as a microporous layer for proton exchange membrane fuel cells. (15th July 2021) - Kim, Jaeyeon; Kim, Hyeok; Song, Hyeonjun; Kim, Dasol; Kim, Geon Hwi; Im, Dasom; Jeong, Youngjin; Park, Taehyun
Abstract: A multi-walled carbon nanotube (CNT) sheet was employed and investigated as a microporous layer (MPL) of proton exchange membrane fuel cell (PEMFC). The CNT sheet was synthesized via floating catalyst chemical vapor deposition method. The CNT sheet MPLs with the thickness of 15, 30, and 100 μm were prepared and compared with a commercial carbon-black MPL. As a result, it was found that the PEMFC with the 15-μm-thick CNT sheet MPL showed high electrochemical performance, and it outtopped the conventional PEMFC. The 15-μm-thick CNT sheet MPL increased the peak power density by 50.9% in air-supplied cathode and 20.9% in pure oxygen-supplied cathode compared to the conventional PEMFC. Through electrochemical impedance analyses, it was found that the CNT sheet MPL effectively decreased a charge transfer resistance, which is attributed to the improved reaction kinetics and mass transport through the MPL. Graphical abstract: Image 1 Highlights: CNT sheet was employed as a microporous layer for PEMFCs. CNT sheet was fabricated via cost-effective floating catalyst CVD method. Electrochemical performance was increased by 20.9%–50.9% through this approach. EIS and SEM were employed to further investigate the performance enhancement.